On Hilbert's Inequality for Double Series and Its Applications. (31st March 2008) - Yu, Zhou; Mingzhe, Gao
Abstract : This study shows that a refinement of the Hilbert inequality for double series can be established by introducing a real functionu ( x ) and a parameterλ . In particular, some sharp results of the classical Hilbert inequality are obtained by means of a sharpening of the Cauchy inequality. As applications, some refinements of both the Fejer-Riesz inequality and Hardy inequality inH p function are given.